2022
DOI: 10.3390/pharmaceutics14112290
|View full text |Cite
|
Sign up to set email alerts
|

An Immunconjugate Vaccine Alters Distribution and Reduces the Antinociceptive, Behavioral and Physiological Effects of Fentanyl in Male and Female Rats

Abstract: Fentanyl (FEN) is a potent synthetic opioid associated with increasing incidence of opioid use disorder (OUD) and fatal opioid overdose. Vaccine immunotherapy for FEN-associated disorders may be a viable therapeutic strategy. Here, we expand and confirm our previous study in mice showing immunological and antinociception efficacy of our FEN vaccine administered with the adjuvant dmLT. In this study, immunized male and female rats produced significant levels of anti-FEN antibodies that were highly effective at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Perhaps more importantly, we observed that immunoglobulin A (IgA) was the best correlate of vaccine-mediated protection from an injected drug challenge, rather than IgG, IgG1, IgG2a or binding affinity [8]. We recently replicated this IgA association with blocking analgesia and reducing brain levels of FEN in rats [19]. IgA is typically thought to prevent mucosal microbial or drug exposures, and our findings about IgA for blocking injected drugs is a critical discovery.…”
Section: Introductionmentioning
confidence: 64%
“…Perhaps more importantly, we observed that immunoglobulin A (IgA) was the best correlate of vaccine-mediated protection from an injected drug challenge, rather than IgG, IgG1, IgG2a or binding affinity [8]. We recently replicated this IgA association with blocking analgesia and reducing brain levels of FEN in rats [19]. IgA is typically thought to prevent mucosal microbial or drug exposures, and our findings about IgA for blocking injected drugs is a critical discovery.…”
Section: Introductionmentioning
confidence: 64%
“…In a preclinical animal study, FEN-CRM + dmLT (a fentanyl-like hapten was combined with the carrier protein CRM197 and an adjuvant derived from heat-labile enterotoxins from E. coli (LT) named dmLT) generated significant amounts of anti-fentanyl antibodies that were associated with a significant blockade of fentanyl’s analgesic effects in mice. In the meantime, cross-reactivity assays demonstrated that anti-fentanyl antibodies exhibit binding affinity to fentanyl and sufentanil, while displaying no binding interaction with morphine, methadone, buprenorphine, or oxycodone [ 15 ]. In another study, Carfen-ester-TT (the methyl ester functional group of carfentanil as the point of linker attachment) and Carfen-p-phenyl-TT (positions the linker at the para position of the phenethyl ring) can effectively target fentanyl and carfentanil, eliciting high-affinity antibodies against both drugs in mice [ 58 ].…”
Section: Recent Progress In Anti-drug Vaccine Researchmentioning
confidence: 99%
“…In the rat, dose–response curves of respiratory effects were shifted to the right with the vaccine, without affecting the ability of naloxone to reverse the respiratory depression [ 81 ]. Vaccinated rats showed improved physiological parameters including oxygen saturation and heart rate after exposure to fentanyl compared to unvaccinated rats [ 82 ]. In comparison to the controls, decreased post-exposure drug levels in the brain were observed in rats vaccinated with F1-CRM, a supported candidate vaccine against fentanyl and selected analogues.…”
Section: Reversal Of the Neurorespiratory Toxicity Induced By Fentany...mentioning
confidence: 99%